(untitled) (مجلة الواحات للبحوث والدراسات, 2022)
ملخص الجزائر من أكثر الدول التي تعرف انتشارا واسعا لظاهرة الفساد ويظهر ذلك من الوضع العام الملاحظ من خلال قضايا الفساد، والرتب المتدنية التي تحصل عليها في المؤشرات التي تصدرها مختلف تقارير الهيئات والمؤسسات الدولية الخاصة بالفساد. حيث يعتبر الفساد من أهم معوقات النمو والتنمية سواءا بطريقة مباشرة أو غير مباشرة. تهدف هذه الدراسة على معرفة تأثير الفساد (مؤشر مدركات الفساد) على النمو الاقتصادي باستخدام بيانات الجزائر للفترة من 2003 إلى غاية 2019 باستعمال نموذج التكامل المشترك، حيث أظهرت نتائج الدراسة تأثير السلبي للفساد على النمو الاقتصادي. وبينت الدراسة أن ارتفاع الفساد بنسبة 1% يؤدي إلى انخفاض في الناتج المحلي الإجمالي بنسبة 0.53%. كلمات دالة: فساد، مؤشر مدركات الفساد، نمو اقتصادي، إنفاق حكومي محلي، نموذج التكامل المشترك. Abstract Algeria is one of the countries that knows a wide spread of the phenomenon of corruption, and this is evident from the general situation observed through corruption cases, and the low ranks it gets in the indicators issued by the various reports of international bodies and institutions on corruption. The Corruption is considered one of the most important obstacles to growth and development, either directly or indirectly. This study aims to know the effect of corruption (Corruption Perceptions Index) on economic growth by using Algeria’s data for the period from 2003 to 2019 using the Johansen cointegration test, as the results of the study showed the negative impact of corruption on economic growth. The study showed that a 1% rise in corruption leads to a 0.53% decrease in GDP. Key words: corruption, corruption perceptions index, economic growth, Domestic Government Spending, cointegration.